Obtenção e caracterização de cimento odontológico a partir da adição de Fosfato Tricálcico ao cimento Portland CPV-Ari - Aguiar, Anne Helena Duarte de (2019)
Biomaterials have been widely used in the medical and dental fields due to their excellent properties. Among the biomaterials, calcium phosphate bioceramics stands out, among which, hydroxyapatite and tricalcium phosphate are the most studied and researched because they are naturally bioactive and exhibit excellent biocompatibility, bioactivity, dissolution rates, absence of toxicity and osteoconductivity (indicate the path for bone growth), thus favoring osteoinduction, osseointegration and bone neoformation when placed in a biological environment. With the advent of nanotechnology it has become possible to use bioceramics as root cements. A biocement that has gained a broad field of use in dentistry was the Mineral Trioxide Aggregate (MTA), which can be used in several dental procedures. The main objective of the present study was to prepare and characterize cements based on Portland CPV-Ari and Tricalcium Phosphate for dental use. Six cements were prepared: in the solid phase, 200g of pure CPV-Ari were used, added to 0.5%, 1%, 2%, 4% and 8% of Triccalcium Phosphate powder and mixed in a ball mill. The liquid phase was maintained at the ratio of 0.27 g of distilled water to all the cements. The cements were inserted into test bodies and the top of the test specimen was maintained in contact with artificial saliva. The cements were characterized at the ages of 7 days (168H) and 28 days (672H), in the top and middle regions of the sample. The techniques used were: Mass Loss and Solubility, Ph, Thermogravimetry, X-ray Fluorescence, X-Ray Diffraction, Scanning Electron Microscopy and Vickers Microhardness. The solubility test showed that most of the cements had solubility below the maximum recommended by ADA standards n.57 and ISO 6876/2001, which is 3%, except for CPV + 2% Tricalcium Phosphate for the experimental time of 28 days. The Ph variation test showed that all the cements provided alkalinity of the medium to which they were exposed, with the highest alkalinity obtained with cement CPV + 4% Tricalcium phosphate. Thermogravimetry showed that all the cements behaved in a similar way, where the mass loss occurred in five stages, and the cement CPV + 8% Tricalcium Phosphate was the one in which the mass loss was the lowest.. The XRF of all the cements showed the formation of the oxides present in the Portland cement, as well as the formation of the diphosphorus pentoxide, where in the top region of the sample in contact with saliva the P2O5/CaO content increased as the Triccalcium Phosphate present in the cement increased. In XRD, the presence of four phases was verified: Etringite; Portlandite; Hatrurite; Hydroxyapatite. The microhardness showed that due to leaching of the cement compounds the region of the top of the sample in contact with the saliva obtained results of microhardness inferior to the regions that were not in contact with the saliva. The SEM shows that all the micrographs of the region exposed to saliva obtained images compatible with those found in the literature of formation of hydroxyapatite. These results suggest that it is possible to develop a dental cement using Portland CPV-Ari + Triccalcium Phosphate